Disruptive Innovation and Economic Value Creation : A Service Sector Perspective - Kar, Surjit Kumar; Padhi, Sunil Kumar; Samantarai, Munmun (Prabandhan: Indian Journal of Management, 2016)
This paper explored the scope of disruptive and reverse innovation in emerging-market context and economic value creation for a sustainable competitive advantage by companies in the service sector. As a conceptual paper, it draws significantly on innovation literature. Illustrative Indian companies/ brands have maneuvered such skills by redefining the accepted innovation logic and cycle. There is symmetry in economic value creation at intermittent stages of the innovation cycle within a global value delivery network. Innovation-led economic value creation is insignificant of geographical subscription. Theory of economics explains the macro environmental factors defying the logic of straight extension to cross border markets and warrants for dual adaptation or new product invention in the host country. Flow of innovation, with timely intervention, can create economic value, and meet both commercial and societal needs. With a growth in venture capital funding for start-ups and kick start of "Make in India" kind of initiative by the government, this study becomes more pertinent.